(untitled) (Research, Society and Development, 2021)
Biology teaching now has new strategies that allow the teacher to improve his classes, his knowledge and transmit them in a dynamic way, mainly through practical classes. The objective of the present study was to verify if practical classes are effective tools for consolidating learning in genetics for students of Youth and Adult Education (EJA). The study was developed in a public school in Timon-MA, in two classes of second stage of the EJA. The results of this research proved that the applied methodology was guiding for the scientific growth of the students of the EJA.